Enhancing Communication Competence Capacity to Achieve Harmonious Families in Jalancagak District, Subang Regency - Rabathy, Qisthy; Komala, Elly; Fitrananda, Charisma; Auliya, Astri; Latifa, Nazwa (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Communication competence encompasses the skills to effectively speak, listen, behave, and act within interpersonal interactions. This competence is particularly vital for mothers, who play a central role in family dynamics. This study aims to enhance the communication skills of family members, focusing on mothers, through training, mentoring, and simulations organized by the Family Welfare Empowerment (PKK) organization in Jalancagak District, Subang Regency. The Community Partnership Program (PKM) facilitated these activities, resulting in a better understanding of the importance of good communication, the crucial role of women in the family, and effective verbal and non-verbal communication. The program notably improved participants' communication skills, fostering more open and coordinated interactions within families and between the PKK group and local government officials. The successful implementation of this program underscores its significance in empowering families and promoting family welfare through enhanced communication competence.